Diary of wimpy kid: No brainer - Kinney, Jeff (London Puffin, 2023)
In Diary of a Wimpy Kid: No Brainer, Greg Heffley returns with another whirlwind adventure as he navigates the ups and downs of middle school life. This time, Greg$1 (Bs main challenge is trying to survive the back-to-school season while dealing with his family's quirks, peer pressure, and the usual academic stress. As he grapples with school projects, unexpected responsibilities, and new school events, Greg faces situations that test his patience, creativity, and resilience. In his classic humorous and somewhat skeptical tone, Greg documents the amusing$1 (Band sometimes frustrating$1 (Bexperiences of growing up, proving once again that middle school is no easy journey.s